Knowledge integration in transdisciplinary research: a case study of the socio-ecological complexity project - Allegretti, Arren Mendezona, author; Laituri, Melinda, advisor; Pickering, Kathleen, advisor; Thompson, Jessica, committee member; Fernandez-Gimenez, Maria, committee member (Colorado State University. Libraries, 2015)
Knowledge integration has been crucial for gaining a holistic picture of the inner workings of socio-ecological systems. Integrating local and scientific knowledge sustains biological and global cultural diversity, and may fill gaps in understanding that cannot be elucidated by individual scientific disciplines. Interdisciplinary and transdisciplinary research teams face the challenge of collaborating and integrating their varying disciplinary paradigms and epistemologies along with stakeholders' local knowledge for understanding and adapting to global and local environmental issues. Communication and knowledge integration across funders, researchers, and research end-users in transdisciplinary research are critical for meeting diverse stakeholder needs and genuinely engaging multiple knowledge systems. These knowledge systems may include a combination of researcher and local ecological knowledge embedded in institutions, disciplines, and cultures. The purpose of this dissertation is to investigate and apply knowledge integration tools for examining socio-ecological systems and transdisciplinary research communication. Specifically, I examine the Socio-ecological Complexity (SEC) project as a case study. The SEC is a pseudonym for an actual project examining the role of Community-Based Rangeland Management (CBRM) institutions in influencing the resilience of Mongolian socio-ecological rangeland systems to climate change. I apply two tools for the integration of knowledge within SEC: participatory reflection and participatory mapping. I apply participatory reflection among the SEC research team and provide stakeholder engagement indicators for reflecting, communicating, and incorporating the needs of funders, researchers, and research end users as major stakeholder groups in transdisciplinary research. These specific indicators allow transdisciplinary research teams to assess the current level of knowledge integration, communicate and target stakeholder needs that may influence project outcomes in communicating their research. To integrate the local ecological knowledge (LEK) of research end users, I apply participatory mapping to explore herders' knowledge of their rangelands and their perceptions of socio-ecological boundaries imbedded in their pastures. The process of participatory mapping revealed emic narratives on physical and human demarcated boundaries influencing landscapes, adaptive practices, and local governance arrangements for accessing pasture resources. Participatory mapping and participatory reflection serve as tools for integrating and communicating diverse knowledge systems in transdisciplinary research. To examine how knowledge and world views may be communicated among diverse actors in transdisciplinary research, I provide a reflexive account of the role of voice in transdisciplinary fieldwork. My reflexive account reveals the complex network of actors and how identity, language, financial structures and hierarchy within a multi-cultural and transdisciplinary project shape actors' voices and opinions. The application of knowledge integration tools (participatory reflection and participatory mapping) and the open dialogue about the role of voice in transdisciplinary research provide diverse views for evaluating transdisciplinary research outcomes and analyzing coupled human-environment relationships in socio-ecological systems.
Keywords: interdisciplinary team communication; knowledge integration; Mongolian rangelands; socio-ecological systems; stakeholder engagement; transdisciplinary research